2020
DOI: 10.1093/mnras/staa3749
|View full text |Cite
|
Sign up to set email alerts
|

GG Carinae: orbital parameters and accretion indicators from phase-resolved spectroscopy and photometry

Abstract: B[ e ] supergiants are a rare and unusual class of massive and luminous stars, characterised by opaque circumstellar envelopes. GG Carinae is a binary whose primary component is a B[ e ] supergiant and whose variability has remained unsatisfactorily explained. Using photometric data from ASAS, OMC, and ASAS-SN, and spectroscopic data from the Global Jet Watch and FEROS to study visible emission lines, we focus on the variability of the system at its ∼31-day orbital period and constrain the stellar parameters o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…We find that the closer ring has a radius of 𝑅 = 2.8 +0.9 −1.1 AU from the binary, and the outer ring has 𝑅 = 27 +9 −10 AU from the binary. As expected, the rings orbit slightly closer into the binary than as reported by Maravelias et al (2018) due to the lower masses of the binary components reported in Porter et al (2021a). These correspond to ∼ 4.7 and 45 semi-major axes of the binary, respectively.…”
Section: Radii Of the Circumbinary Ringssupporting
confidence: 72%
See 4 more Smart Citations
“…We find that the closer ring has a radius of 𝑅 = 2.8 +0.9 −1.1 AU from the binary, and the outer ring has 𝑅 = 27 +9 −10 AU from the binary. As expected, the rings orbit slightly closer into the binary than as reported by Maravelias et al (2018) due to the lower masses of the binary components reported in Porter et al (2021a). These correspond to ∼ 4.7 and 45 semi-major axes of the binary, respectively.…”
Section: Radii Of the Circumbinary Ringssupporting
confidence: 72%
“…Marchiano et al (2012) finds that the dust envelope begins at ∼ 230 𝑅 pr . Using 𝑅 pr = 27 +9 −7 𝑅 from Porter et al (2021a), this corresponds to the dust envelope radius of 29 +10 −7 AU. This places the outer O I ring in a similar region to the inner edge of the system's dust envelope.…”
Section: Radii Of the Circumbinary Ringsmentioning
confidence: 99%
See 3 more Smart Citations